PENCARIAN RUTE TERPENDEK PERJALANAN PROMOSI MARKETING MENGGUNAKAN ALGORITMA GENETIKA DAN ALGORITMA GREEDY - Dini Silvi Purnia; Dwiza Riana (Jurnal Informatika, 2016)
ABSTRACTA promotional team are doing promotions to schools in determining travel routes are still having trouble of having to find the shortest distance of the school will be visited. In the resolution of an efficient service, required a system with a method that can help in determining the fastest route. Method of comparison is a genetic algorithm and greedy algorithm for the genetic algorithm is a method by using variable speed in every way that affects travel time each way and take advantage of the natural selection process that is known as an evolutionary process, this process has the function of crossover, mutation and individual improvement, using processes are largely carried out randomly then produced the best solution in the process of finding the fastest route. Has made the application of genetic algorithm and greedy algorithm for determining the shortest route compose a promotional trip PMB AMIK BSI Tasikmalaya which generates the most optimal route. Has made a comparison between the genetic algorithm and greedy algorithm in the most optimal route search The comparison showed that the genetic algorithm is an algorithm that is more appropriate to determine the route of travel promotion than the greedy algorithm..Keywords: genetic algorithm, greedy algorithm, shortest path